The effect of IFRS convergence and the proportion of woman in audit committee on earning management - Siswanti, Dwi Surti; Hudayati, Ataina (2017)
This study aims to find empirical evidence the effect of IFRS convergence and the proportion of woman in audit committee on earning management.Respondents used in this study were companies listed in Jakarta Stock Exchange for the year 2011 until 2013. Using moderated regression analysis this study supports the hypothesis that IFRS convergence and the proportion of woman in audit committee have negative effect on earning management.This finding implies that IFRS convergence and the proportion of woman in audit committee will increase the quality of financial reporting.